STRATEGI PENGELOLAAN DAN ANALISIS STATUS KEBERLANJUTAN KETAHANAN PANGAN DI KABUPATEN HALMAHERA TENGAH - Syafruddini; Surjono Hadi Sutjahjo; Yayuk Farida Baliwati; Rita Nurmalina (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2007)
The aim of the research is to construct the planning of the desirable dietary based on potential area in sustainability food security development frame. This research was done on a survey research basis. The types of data consist of primary and secondary data. The Rapfish method was used for continuing analysis, whereas the Analysis Hierarchy Process (AHP) method was used to decide the strategy for sustainability food security management. The results of this research are: I) the sustainability index or scales value of ecology dimension falls into "good" category, the cultural-society dimension is in -fine" category and the economy dimension is included in "less" category. And (2) Management strategy in an attempt to achieve the sustainability of food security in Central Halmahera is 'low food price' as the first priority, this is then followed by the increases of food production, farming incentive, friendl environmental in agriculture, eradication of poor society, and the improvement of human resource quality Key words: management strategy, food security, sustainability, Central Halmahera.   Penelitian ini bertujuan untuk menyusun perencanaan pangan harapan berbasis potensi wilayah dalam kerangk pembangunan ketahanan pangan berkelanjutan. Penelitian ini merupakan penelitian survey. Jenis data yank digunakan adalah data primer dan data sekunder. Untuk analisis keberlanjutan digunakan metode rapfish selanjutnya untuk menentukan strategi pengelolaan ketahanan pangan digunakan metode Analysis Hierarchy Proces (AHP). Hasil penelitian menunjukkan bahwa: 1) Nilai indeks keberlanjutan dimensi ekologi termasuk kategori baik dimensi sosial-budaya termasuk kategori cukup dan dimensi ekonomi termasuk kategori kurang berkelanjutan pa skala sustainabilitas, 2) Strategi pengelolaan dalam upaya pencapaian ketahanan pangan berkelanjutan di Kabupaten Halmahera Tengah adalah harp pangan murah sebagai prioritas pertama, diikuti peningkatan produksi pangan insentif usahatani, pertanian ramah lingkune,an, pengentasan kemiskinan dan peningkatan kualitas SDM. Key words: strategi manajemen, ketahanan pangan, keberlanjutan, Halmahera Tengah